Pendidikan Literasi Finansial dalam Penguatan Karakter Santri Islamic Boarding School - Alfin Maskur; Ansori, Miksan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study examines the implementation of financial literacy education in strengthening the character of students at Islamic Boarding School SMPI Al A'la Loceret Nganjuk. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that financial literacy is effectively integrated through three dimensions: financial knowledge, attitudes, and behavior, all grounded in Islamic values such as qana’ah (contentment), amanah (trustworthiness), and responsibility. The school's contextual approach, including pocket money management systems and savings practices, has successfully fostered disciplined and ethical financial habits among students. While the program focuses on basic financial concepts, it demonstrates the potential of Islamic Boarding Schools to develop value-based financial literacy. This study contributes to the literature by highlighting an alternative model of financial education that combines practical skills with character building, offering insights for Islamic educational institutions seeking to enhance their students' economic and moral competencies.